The combined effect of taxation and subsidization on human capital investment - Salvatore Barbaro (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2003)
The impact of fiscal activity on human capital formation has often been analyzed with regard to the expenditure side of the budget, i.e. the subsidization of (higher) education. Recent contributions have increasingly focused on the effect of taxation on human capital accumulation. Less attention is given to the simultaneous effect of both subsidization and taxation on human capital accumulation. Since subsidies to higher education may offset the distortionary effects of taxation, the paper aims to analyze the amount of subsidization which is necessary to counteract the discouraging effect of various kinds of taxation (i.e., proportional, direct, indirect taxation and a combination of both direct and indirect taxation) on human capital, measured as the graduation rates. Furthermore, the effect of externalities from higher education on the optimal amount shall be analyzed as well as the role of taxation if direct costs of higher education are completely born by the state. The framework we use to illustrate our point is an two period cohort model with heterogeneous agents who endogenously decide on higher education with respect to taxation and subsidization.
Keywords: 330; Bildungsinvestition; Subvention; Öffentliche Bildungsausgaben; Einkommensteuer; Steuerwirkung; Deutschland